ANALISIS KEBUTUHAN PENGEMBANGAN E-MODUL BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Nadira (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This study aims to analyze the needs for developing Project Based Learning (PjBL)-based e-modules to enhance high school students’ critical thinking skills. A descriptive qualitative method was used, with data collected through classroom observations and interviews with physics teachers and students of grades XI and XII at MAN 2 Tebo. The results showed that physics learning is still dominated by the lecture method, with textbooks and student worksheets as the primary learning resources. Teachers have never used e-modules or fully implemented PjBL due to limited understanding of the model syntax and insufficient facilities. The most difficult material for students to understand is Thermodynamics, especially concepts such as internal energy, entropy, and thermal cycles, which are considered abstract and hard to visualize. Students expressed difficulties due to the lack of real examples and limited use of interactive media. They expect interactive digital learning resources equipped with animations, experiment videos, visual summaries, and exercises. Classroom observations also revealed limited technological infrastructure, such as few computers and projectors, as well as restrictions on mobile phone use. These findings emphasize the need to develop PjBL-based e-modules as an alternative learning medium to support contextual and engaging physics learning and foster students’ critical thinking skills in line with the Merdeka Curriculum.